2017
DOI: 10.4172/0974-8369.1000412
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Screening, Antioxidant, Anti-inflammatory, and Glucose Utilization Activities of Three South African Plants Used Traditionally to Treat Diseases

Abstract: Medicinal plants are important in the treatment of human diseases. The medicinal properties of plants are attributed to the presence of secondary plant metabolites. Polyphenols, particularly fl avonoids, are phytochemicals that possess antioxidant and anti-infl ammatory activity, and modulate pathways involved in obesity and glucose metabolism. In folk medicine, a single plant may be used to treat various diseases owing to the presence of phytochemical varieties in plants. In this study, the acetone leaf extra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
16
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 38 publications
2
16
0
1
Order By: Relevance
“…3-fold more (p < 0.05) total phenolics than the QLD samples (Table 4). The results of the present study are similar to the reported TPC in leaves and twigs of other species belonging to the Pittosporaceae family, ranging from 2600 to 4090 mg GAE/100 g DW [42][43][44][45]. However, compared to…”
Section: Total Phenolic Content (Tpc)supporting
confidence: 90%
See 1 more Smart Citation
“…3-fold more (p < 0.05) total phenolics than the QLD samples (Table 4). The results of the present study are similar to the reported TPC in leaves and twigs of other species belonging to the Pittosporaceae family, ranging from 2600 to 4090 mg GAE/100 g DW [42][43][44][45]. However, compared to…”
Section: Total Phenolic Content (Tpc)supporting
confidence: 90%
“…3-fold more (p < 0.05) total phenolics than the QLD samples ( Table 4). The results of the present study are similar to the reported TPC in leaves and twigs of other species belonging to the Pittosporaceae family, ranging from 2600 to 4090 mg GAE/100 g DW [42][43][44][45]. However, compared to green tea leaf powder, a popular source of polyphenols, the TPC in the studied P. angustifolium samples was lower (730-4075 mg GAE/100 g DW vs. 6500-10,600 mg/100 g DW [46]).…”
Section: Total Phenolic Content (Tpc)supporting
confidence: 90%
“…Another pivotal feature of these natural metabolites is their structural diversities which also allow them to render versatile biological functions like antioxidant, antimicrobial, cytotoxic, anti-inflammatory properties etc. as well 1,2,3 .…”
mentioning
confidence: 94%
“…Total phenolic content of extracts was determined using the 96-well plate by method previously described (Olaokun et al, 2017). To extracts (20 μl) in a 96-well plate was added 100 μl of 20% Folin-Ciocalteu reagent and 80 μl of 7.5% sodium bicarbonate solution.…”
mentioning
confidence: 99%
“…Total flavonoid content of extracts was determined using the 96-well plate method (Olaokun et al 2017). To extracts (100 μl) in a 96-well plate was added 100 μl of 2% aluminium chloride.…”
mentioning
confidence: 99%